Contemporary Islamic Family Law Studies: An Analysis of the Inconsistency of Marriage Age Limits Between Law and Social Reality at the Mojokerto Religious Court - Dwi Ratna Cinthya Dewi; Durrotul Fikriyah; Muhammad Dzul Hilmi Utsman; Marlinda Ayu Ningsih; Alhafidh Nasution (Legitima : Jurnal Hukum Keluarga Islam, 2024)
Purpose - This study examines the inconsistency of the marriage age limit as regulated in the Marriage Law and PERMA Number 5 of 2019 concerning Reasons for Adjudicating Marriage Dispensation Cases. In addition, this study also analyzes the views of judges at the Mojokerto Religious Court regarding the application of marriage dispensation. It explores the dynamics of social reality that influence the practice of contemporary Islamic family law. Methods - This research is field research with an empirical juridical approach. Research is conducted by interviewing judges, lawyers, the community, and the Head of the Religious Affairs Office and analyzing laws and regulations. The analysis was carried out to identify inconsistencies in the rules for marriage age limits and marriage dispensation contained in Article 7 paragraph (2) of Law Number 16 of 2019 with PERMA Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Applications. Findings - This study concludes several findings: first, the scholars' opinions on the age limit of marriage vary, but some scholars have agreed to determine it as a means of mashlahah to answer problems in the contemporary era. Second, there are legal inconsistencies between Article 7 paragraph (2) of Law Number 16 of 2019 and PERMA Number 5 of 2019, namely the age limit for marriage and the application for marriage dispensation. Research Implications - The regulations on marriage dispensation have indeed been explained, but there is still a lack of clarity regarding the urgent reasons for applying. Therefore, detailed clarity is needed to answer these reasons so as not to cause legal disharmony and legal uncertainty.